Deep neuromuscular block improves surgical conditions during laparoscopic hysterectomy: a randomised controlled trial - Dubois, Philippe E; Putz, Laurie; Jamart, Jacques; Marotta, Maria-Laura; Gourdin, Maximilien; Donnez, Olivier (European journal of anaesthesiology, 2014)
The benefit of inducing deep neuromuscular block to improve laparoscopic surgical conditions is controversial. The goal of this study was to determine the depth of neuromuscular block needed to guarantee excellent operating conditions during laparoscopic hysterectomy. A randomised controlled trial. A single-centre study performed between February 2011 and May 2012. One hundred and two women of ASA physical status 1 or 2 gave consent to participate and were allocated randomly to one of two groups. Under desflurane general anaesthesia, patients in Group S (shallow block), neuromuscular blockade was induced by administration of rocuronium 0.45 mg  kg-1 followed by spontaneous recovery or a rescue bolus dose of 5  mg if surgical conditions were unacceptable. In Group D (deep block), neuromuscular block was induced by administration of rocuronium 0.6 mg  kg-1 and maintained by bolus doses of 5  mg if the train-of-four count exceeded two, using adductor pollicis electromyography. With a stable pneumoperitoneum (13 mmHg), the surgeon scored the quality of the surgical field every 10  min as excellent (1), good but not optimal (2), poor but acceptable (3) or unacceptable (4). The groups were compared using the Cochran-Armitage trend test. The level of neuromuscular blockade was recorded each time the surgical field score exceeded 1. For groups S and D, respectively, the maximum surgical field scores were 1 in 21 and 34 patients, 2 in 11 and 11 patients, 3 in 4 and 5 patients and 4 in 14 and 0 patients. A trend towards higher scores was demonstrated in group S (P < 0.001). Surgical field scores of 2, 3 and 4 occurred only when the train-of-four count was at least 1, 2 and 3, respectively. Inducing deep neuromuscular block (train-of-four count <1) significantly improved surgical field scores and made it possible to completely prevent unacceptable surgical conditions.